(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
The antinociceptive activity of the methanolic extract of the barks of Tamarix indica Roxb. was investigated using acetic acid-induced writhing model in swiss albino mice. The extract produced about 26.89%( P< 0.01) and 43.55% (P< 0.001) writhing inhibition at the dose of 250 and 500 mg/ kg of body weight respectively, which was comparable to the standard drug diclofenac sodium where the inhibition was about 63.64% (P< 0.001) at the dose of 25 mg/kg of body weight. At the above doses, the extract exhibited significant and dose dependent antinociceptive activity in acetic acid-induced writhing model in swiss albino mice. Phytochemical investigation of the extract indicate the presence of reducing sugars, tannins, gums, flavonoids and saponin. Key words: Tamarix indica; antinociceptive activity; acetic acid-induced writhing; phytochemical test. DOI: 10.3329/bjpp.v25i1.5736 Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 1-3